2019
DOI: 10.1016/j.devcel.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Population and Single-Cell Analysis of Human Cardiogenesis Reveals Unique LGR5 Ventricular Progenitors in Embryonic Outflow Tract

Abstract: Highlights d Comprehensive gene expression profiles on human cardiogenesis are reported d LGR5 is identified as a key regulator on human-specific conoventriculogenesis d LGR5 signaling may be associated with certain human congenital heart diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 49 publications
(80 reference statements)
4
103
1
Order By: Relevance
“…Future studies should determine if this occurs with this common human coding variant of C5ORF46. Prior studies have identified links between C5ORF46 and either heart disease, or heart development (46,47). This agrees with the expression profile in human tissues and cells, where C5ORF46 is detectable at the RNA-level in major blood vessels (aorta) and the heart, but also in skin and salivary gland ( Fig.…”
Section: E G S D K N P E K P D E K P a D S G K S P E K P D D K P D D supporting
confidence: 86%
“…Future studies should determine if this occurs with this common human coding variant of C5ORF46. Prior studies have identified links between C5ORF46 and either heart disease, or heart development (46,47). This agrees with the expression profile in human tissues and cells, where C5ORF46 is detectable at the RNA-level in major blood vessels (aorta) and the heart, but also in skin and salivary gland ( Fig.…”
Section: E G S D K N P E K P D E K P a D S G K S P E K P D D K P D D supporting
confidence: 86%
“…Isl1 has a well-established role in mammalian cardiac development and is expressed in multipotent cardiovascular progenitor cells in mice [39][40][41] and humans [42,43]. Despite its established role in heart development in mice, loss of function variants in the ISL1 locus are drastically underrepresented in large human cohorts of congenital heart malformations like the Pediatric Cardiac Genomics Consortium (PCGC) [28,44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GINS3 is enriched in these cells, which is known to participate in the regulation of cardiac repolarization 71,72 . NC3 and NC4 subpopulations shared a broadly similar transcriptional profile including LGR5 , a G-protein-coupled receptor involved in Wnt -signaling that promotes CM differentiation 73 and demarcates a subset of CM in the outflow tract 74 ; this region often becomes arrhythmogenic in heart disease 75 . These cells also expressed genes associated with coronary artery disease, PPP2R2B 76 , LSAMP 77 and LPL an endothelial enzyme involved transporting lipoproteins into the heart 78 .…”
Section: Nc1 Was Distinguished By Enriched Expression Ofmentioning
confidence: 99%